(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The famous metropolis of the Multan was originally situated on the Ravi. It was a walled city with a strong fortress situated on opposite banks of an old course of the Ravi which now flows between the city as well as around it.[1] Multan was known by several names but all of them referred either to God Vishnu or the Sun.